2010
DOI: 10.1007/s00018-010-0272-3
|View full text |Cite
|
Sign up to set email alerts
|

Ordered transcriptional factor recruitment and epigenetic regulation of tnf-α in necrotizing acute pancreatitis

Abstract: Tauhe expression of the critical initiator cytokine TNF-alpha was strongly upregulated in vivo in acute necrotic pancreatitis (AP) in rodents and in vitro in TNF-alpha activated acinar AR42J cells. Upregulation of tnf-alpha, inos, icam-1 and il-6 occurred both in TNF-alpha receptor 1 and 2 knock-out mice, but not in TNF-alpha knock-out mice, in cerulein-induced acute pancreatitis. Chromatin immunoprecipitation analysis showed that transcriptional factors (ELK-1, SP1, NF-kappaB and EGR-1) and chromatin modifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 53 publications
1
25
0
Order By: Relevance
“…In agreement with the histone H3 acetylation, Ad-shS1/FliC DCs also exhibited ∼6-fold increase in recruitment to the TNF-α promoter of the transcription factor sp1 ( Fig. 3B ), which was demonstrated to be important in LPS-stimulated TNF-α expression in several previous studies [28], [29]. We also found that histone H3 acetylation and sp1 recruitment to the TNF-α promoter in the Ad-shS1-transduced BMDCs were lower than those in the Ad-shS1/FliC-transduced BMDCs, but apparently higher than those in the LPS-stimulated BMDCs ( Fig.…”
Section: Resultssupporting
confidence: 88%
“…In agreement with the histone H3 acetylation, Ad-shS1/FliC DCs also exhibited ∼6-fold increase in recruitment to the TNF-α promoter of the transcription factor sp1 ( Fig. 3B ), which was demonstrated to be important in LPS-stimulated TNF-α expression in several previous studies [28], [29]. We also found that histone H3 acetylation and sp1 recruitment to the TNF-α promoter in the Ad-shS1-transduced BMDCs were lower than those in the Ad-shS1/FliC-transduced BMDCs, but apparently higher than those in the LPS-stimulated BMDCs ( Fig.…”
Section: Resultssupporting
confidence: 88%
“…The ChIP and RNApol ChIP procedures were performed according to Sandoval and co-workers [58], [59], and Rodriguez and co-workers [33], [60] with some modifications. Livers were surgically removed from anaesthetized animals, washed in PBS and fixed by immersion in 1% formaldehyde in PBS under rotation during 15 min at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Cerulein-induced pancreatitis might involve TNF signaling, since neutralization of TNF with the TNF blocker Etanercept attenuates cerulein-induced pancreas necrosis [105]. Moreover, the induction of inflammatory effectors such as IL-6 and iNOS is reduced in cerulein-treated TNF -/- mice [106]. Importantly, RIP3 -/- mice were also resistant to cerulein-induced pancreatitis [36, 37].…”
Section: Necrosis In Chemical- and Trauma-induced Cell Injurymentioning
confidence: 99%